AB1198 EVALUATION OF THE WAITING TIME AND QUALITY OF RHEUMATOLOGY REFERRAL AT A TERTIARY CARE CENTER OF PORTO ALEGRE – RS, BRAZIL. (June 2019) - Busato, Vanessa; Piovesan, Deise; Silveira, Romulo; Hickmann, Sheila; Bongiorno, Guilherme; Cruz, Camila; Zamboni, Sheron; Simon, Julio; Bredemeier, Markus
Abstract : Background: To improve waiting time for a first consultation with a rheumatologist has become an important challenge in many countries [1, 2]. In 2008, a previous survey [3] evaluating the referrals to our Service, we observed long waiting times (median 3.8 months, interquartile range (IQR)=1.5-10.0, ranging from 3 days to 8 years) and that only 31% of consultations were related to hypothesis of systemic inflammatory rheumatic diseases (SIRD), which should be properly managed at a resourceful tertiary care center. In 2015, a new process of triage for referrals (based on a protocol recording relevant information and judgment by a rheumatologist) was introduced in our state health system aiming to improve quality of referrals and reduce waiting lists [4]. However, this system is applied only for patients from cities other than the capital (Porto Alegre, RS). Objectives: To evaluate the waiting time and quality of referral for first Rheumatology consultations at a tertiary care center of South Brazil, comparing the present results with those obtained 10 years ago in a similar survey [3]. Methods: In a cross-sectional study, information regarding all first consultations at the Rheumatology Service of Hospital Nossa Senhora da ConceiÇão were prospectively collected from Oct 2017 to Mar 2018. Referred patients were characterized in terms of demographic features, diagnostic hypothesis formulated by the rheumatologist and time from initial referral. For analytical purposes, patients with adequate referrals were considered to be those that presented high probability of SIRD, needing assistance at secondary or tertiary level of care. The results were compared with data collected in the same way in 2008 [3]. Chi-square test was used for statistical analysis. Results: Of 444 appointments for scheduled for new patients, 87 (19%) did not attend. The features of the remaining 357 patients were: female=85%, mean (SD) age= 53 (15) years. The waiting time for consultation ranged from 7 days to 63, 8 months (median 12.7, IQR= 4.4-14.1). Diagnostic suspicion of SIRD occurred in 186 (52%). Among SIRD, rheumatoid arthritis (23, 5%) was the most frequent, while among non-SIRD, osteoarthritis (21, 0%) and fibromyalgia (20.7%) were the most common diagnostic hypotheses. A SIRD was the main hypothesis in 75/193 (38.9%) patients from the capital, comparing with 111/174 (67, 7%) among those from other cities (P<0, 001), indicating better selection of the latter group of patients. A reanalysis of data colleted in 2008 revealed that, at that time, the prevalence of suspected SIRD was not significantly different between patients from capital (76/262, 29.0%) and those from other cities (74/225, 32, 9%; P=0.354). Conclusion: We observed improvement in the quality of referrals from other cities comparing to those from the capital of our state, suggesting a better selection process in the former [4]. Despite the efforts to reduce the waiting time for Rheumatology consultations, we observed an increase when compared to 2008. We believe that the delay is secondary to an increase of the demand without a proportional increase in the number of rheumatologist in the public health system. The elaboration of guidelines with standardized information required for referral and triage process seems to be promising to improve access to consultations in Rheumatology. References: [1] Widdifield J, et al. Arthritis Care Res (Hoboken) 2017;69:104-114. [2] Villeneuve E, et al. Annals Rheum Dis 2013;72: 13-22. [3] Simon, et al. Revista Amrigs 52(4):303-308 [4] Harzheim E, et al. TelessaúdeRS-UFRGS, 2016. Available at: https://www.ufrgs.br/telessauders/documentos/protocolos_resumos/protocolos_encaminhamento_reumatologia_TSRS_20160324.pdf Disclosure of Interests: None declared